2010
DOI: 10.2134/jeq2009.0210
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Arsenic and Phosphorus in Ditch Flow from Litter‐amended Soils and Barn Areas

Abstract: Little is known about the fate of arsenic (As) in land-applied litter from chickens that have been fed roxarsone, an organic feed additive containing As. This study seeks to elucidate the transfer of As in runoff from ditch-drained soils of the poultry-producing region of the Delmarva Peninsula by tracking As and phosphorus (P) export from seven drainage ditches over two water-years (1 July 2005 to 30 June 2007). Annual losses of As from ditches ranged from 0.004 to 0.071 kg ha(-1) while P losses ranged from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Notably, most concentrations of As in surface runoff for all methods of litter application were above the EPA Standard for drinking water (0.01 mg L -1 [0.01 ppm] As) for both rainfall events (USEPA 2009), with one observed concentration for the broadcast Rainfall end treatment measured as seven times greater. In a previous investigation of As fate at the UMES Research and Teaching Farm (source of the soils used in this study), Church et al (2010) found comparable concentrations in ditch runoff. Mercury concentrations in surface runoff (figure 5) during the first event stand in contrast to those observed for As and Zn.…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…Notably, most concentrations of As in surface runoff for all methods of litter application were above the EPA Standard for drinking water (0.01 mg L -1 [0.01 ppm] As) for both rainfall events (USEPA 2009), with one observed concentration for the broadcast Rainfall end treatment measured as seven times greater. In a previous investigation of As fate at the UMES Research and Teaching Farm (source of the soils used in this study), Church et al (2010) found comparable concentrations in ditch runoff. Mercury concentrations in surface runoff (figure 5) during the first event stand in contrast to those observed for As and Zn.…”
Section: Methodssupporting
confidence: 54%
“…Much of this concern centers on litter's contribution of nutrients to runoff. However, there is growing concern over the potential for land-applied litter to contribute other contaminants to runoff water (Kingery et al 1994;Moore 1998;Gupta and Charles 1999;Church et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, research strongly suggests that roxarsone toxicity is highly dependent on inorganic arsenical species, such as As(III) (Chen et al 2011;Church et al 2010) and several organoarsenical derivatives such as monomethyl arsenite (MMA), dimethyl arsenate (DMA-V), arsenite dimethyl (DMA-III) and trimethyl arsine oxide (TMAO) (Dauwe et al 2000). The present work demonstrates that also microorganisms present in underground water can biotransform roxarsone into toxic products, and that toxicity is increased when roxarsone is leached before being incorporated into the underground water.…”
Section: Discussionmentioning
confidence: 99%
“…This was illustrated in a recent controlled laboratory study where Ca phosphate was precipitated in preference to Ca arsenate when Ca was limiting (Neupane and Donahoe 2013). This nonselectivity of materials that use adsorption as their primary mechanism of DP removal could be an advantage in landscapes where arsenic containing compounds, such as roxarsone or nitarsone, have long been used or continue to be used in poultry feed (Garbarino et al 2003;Church et al 2010Church et al , 2011. It could also be a disadvantage in landscapes where other similar competing ions to DP could, over time, fill sorption sites, thus reducing the effectiveness of the amendment to sorb DP.…”
mentioning
confidence: 99%